Peer-instruction and drawing as student activating teaching in SAU24 - Lykke Lind, Barbara (Improving University Science Teaching and Learning, 2023)
In this project report I present my experience with introducing student activities in my sau24 teaching. I describe some methods to activate students and explain how a few of these were applied to four classes taught in the neurophysiology course on the faculty of health in the fall 2017. The feedback from the students is then presented in an evaluation of the approach with regards to participation, learning, which activities the student preferred and how well they were implemented.